Does siPantau Bumil GIS-Based Able to Increase K6 Visits and Reduce Complication for High-Risk Pregnant Women? - Fatmawati, Happy Ika; Sumarni, Sri; Ekoningtyas, Endah Aryati (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2024)
K6 visits and obstetric complications scope is one indicator of maternal health program services. Scarcely have these indicator’s achievements met the expected targets so innovation is needed to improve them. The method that can be used to increase the accomplishment is digitalization, through the use of applications to provide and improve the health services quality in monitoring pregnant women. The objective is to design and investigate the GIS (Geographical Information System) influence on pregnancy monitoring practice, especially on K6 visits and pregnant women’s high-risk obstetric complications in Pekalongan City. This research uses the Research and Development (R&D) method with a quasi-experimental research design and posttest control group design. The population is pregnant women with high-risk factors at 32 weeks gestation in Pekalongan City. The total sample is 60 people, who were divided into two groups, namely 30 respondents in the intervention group and 30 respondents in the control group. In the intervention group, pregnant women were given monitoring through the Sipantau Bumil application and K6 visit notifications, while in the control group, the K6 visit schedule was written in the KIA book. Moreover, the data analysis used the Chi-Square test. The result is the siPantau Bumil application has increased K6 visits with a significance value of p-value=0.012 (p<0.005). In addition, it also reduces obstetric complications with a significance value of p-value=0.002 (p<0.005). The conclusion is the GIS-based pregnancy monitoring application can increase K6 visits and reduce obstetric complications.